2007
DOI: 10.1016/j.molcel.2007.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Balancing BMP Signaling through Integrated Inputs into the Smad1 Linker

Abstract: FGF and other Ras/MAPK pathway activators counterbalance BMP action during neurogenesis, bone formation, and other aspects of vertebrate development and homeostasis. BMP receptors signal through C-terminal phosphorylation and nuclear translocation of the transcription factor Smad1, whereas MAPKs catalyze inhibitory phosphorylation in the Smad1 linker region. Here we show that linker phosphorylation restricts Smad1 activity by enabling Smad1 recognition by the HECT-domain ubiquitin ligase Smurf1. Besides causin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
437
2
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 383 publications
(468 citation statements)
references
References 59 publications
(89 reference statements)
23
437
2
1
Order By: Relevance
“…Recently, importance of the cross-talk between Ras and TGF-␤ signaling pathways has been reported, although roles of Ras signaling on TGF-␤ signaling appear to be context-dependent (Gotzmann et al, 2002;Peinado et al, 2003). Smad1 is phosphorylated by Ras-activated ERK MAP kinases and degraded by Smurf1 (Sapkota et al, 2007), whereas Smad2/3 are irregularly translocated to the nucleus in certain cancer cells transfected with active Ras (Yamagata et al, 2005;Oft et al, 2002). Interestingly, it was reported that TGF-␤-induced EMT was found only in the presence of active Ras (Gotzmann et al, 2002), suggesting that Ets1 would be a key molecule for the cross-talk between TGF-␤ and Ras signaling pathways.…”
Section: Ets1 and Id Proteins Act As Upstream Factors For Sip1 And ␦Ef1mentioning
confidence: 99%
“…Recently, importance of the cross-talk between Ras and TGF-␤ signaling pathways has been reported, although roles of Ras signaling on TGF-␤ signaling appear to be context-dependent (Gotzmann et al, 2002;Peinado et al, 2003). Smad1 is phosphorylated by Ras-activated ERK MAP kinases and degraded by Smurf1 (Sapkota et al, 2007), whereas Smad2/3 are irregularly translocated to the nucleus in certain cancer cells transfected with active Ras (Yamagata et al, 2005;Oft et al, 2002). Interestingly, it was reported that TGF-␤-induced EMT was found only in the presence of active Ras (Gotzmann et al, 2002), suggesting that Ets1 would be a key molecule for the cross-talk between TGF-␤ and Ras signaling pathways.…”
Section: Ets1 and Id Proteins Act As Upstream Factors For Sip1 And ␦Ef1mentioning
confidence: 99%
“…Smurf1 was found to selectively bind to linker-phosphorylated Smad1. Not only did this result in the ubiquitination and specific degradation of linker-phosphorylated Smad1, Smurf1 binding also blocked nucleoporin-Smad1 interactions and subsequent Smad1 nuclear translocation [46]. These data finally provide one firm mechanism as to how linker phosphorylation can restrict Smad1 activity.…”
Section: Regulation Of R-smads By the Ubiquitin-proteasome Pathway Anmentioning
confidence: 74%
“…Originally discovered in a yeast two-hybrid screen using Smad1 as bait, Smurf1 can ubiquitinate BMPspecific Smads 1 and 5, but not TGF-β-specific Smads 2 and 3, targeting them for degradation [44,45]. A recent report by Sapkota et al elegantly demonstrates how different Smad posttranslational modifications can converge in regulating Smad signaling, by revealing interplay between Smad1 linker phosphorylation and Smurf1-dependent ubiquitination [46]. Smurf1 was found to selectively bind to linker-phosphorylated Smad1.…”
Section: Regulation Of R-smads By the Ubiquitin-proteasome Pathway Anmentioning
confidence: 99%
“…Further, the E-3 ligase Smurf1 has been shown to bind preferentially to Smad1 that is phosphorylated in the linker region, targeting it for degradation. (36) Recently, an additional level of complexity in understanding the importance of Smad1 linker-region phosphorylation has been added with the identification of R-Smad linker phosphatases that have site specificity. (37) Less is known about linker-region phosphorylation of Smad6.…”
Section: Discussionmentioning
confidence: 99%